Investigation of zonal flows by using the collective scattering measurement of density fluctuations. (30th July 2015) - Shen, H.G.; Yu, Y.; Lan, T.; Li, Y.D.; Liu, A.D.; Xie, J.L.; Liu, W.D.; Yu, C.X.; Zhang, W.Y.; Ti, A.; Li, J.G.
Abstract: The poloidal rotation velocities in the core plasma region are studied using the instantaneous frequency method (IFM) with the density fluctuations measured by the CO2 laser collective scattering diagnostics on the HT-7 tokamak. A coherent mode is observed in the fluctuations of poloidal velocities with the mode frequency from 10 to 20 kHz. It is identified as geodesic acoustic mode (GAM) zonal flow with poloidal symmetry ( m = 0) and its mode frequency coinciding with the theoretical expected GAM frequency. The nonlinear interactions are investigated by applying the envelope analysis on the density fluctuations. The results confirm that the envelope modulation in the high frequency density fluctuations only comes from the shearing by GAM. The comparison between IFM and envelope analysis is also discussed.